2015
DOI: 10.3109/09513590.2015.1065482
|View full text |Cite
|
Sign up to set email alerts
|

Irisin plasma concentration in PCOS and healthy subjects is related to body fat content and android fat distribution

Abstract: Irisin (Ir), a recently identified adipo-myokine, cleaved and secreted from the protein FNDC5 in response to physical activity, has been postulated to induce the differentiation of a subset of white adipocytes into brown fat and to mediate the beneficial effects on metabolic homeostasis. Metabolic syndrome (MS), a cluster of factors leading to impaired energy homeostasis, affects a significant proportion of subjects suffering from polycystic ovary syndrome (PCOS). The aim of our study was to investigate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
1
35
1
Order By: Relevance
“…Previous studies have shown a positive correlation between Ir levels and BMI and other components of metabolic syndrome, such as systolic blood pressure, FPG level, and TG concentration [35,36]. In another study by our group, Ir was positively associated with metabolic syndrome, FPG, and BMI in relatively young women with polycystic ovarian syndrome (PCOS) [37]. Similarly, a recent study in obese children reported Ir was positively correlated with FIC, HO-MA-IR, and impaired glucose tolerance [25].…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have shown a positive correlation between Ir levels and BMI and other components of metabolic syndrome, such as systolic blood pressure, FPG level, and TG concentration [35,36]. In another study by our group, Ir was positively associated with metabolic syndrome, FPG, and BMI in relatively young women with polycystic ovarian syndrome (PCOS) [37]. Similarly, a recent study in obese children reported Ir was positively correlated with FIC, HO-MA-IR, and impaired glucose tolerance [25].…”
Section: Discussionmentioning
confidence: 54%
“…In the current study, PCOS women had similar plasma irisin concentrations in comparison to the control group. In the literature, the characterization of irisin in PCOS is quite controversial since normal (44), increased (18,21,23) and decreased (16) irisin concentrations have been described in these patients. This inconsistency may be partly due to differences in the assay methods, but it may also be due to the interference of confounding variables associated with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have since disputed the potential of irisin as a therapeutic strategy, based partly on the finding that circulating irisin levels are increased in obese patients. These discrepancies, reviewed in depth by Crujeiras et al [229], are as of yet unresolved and warrant further investigation, particularly due to the finding that irisin is also an adipokine and therefore any association with adiposity must be carefully dissociated from fat mass itself [228][229][230][231][232]. Another circulating factor, fibroblast growth factor 21 (FGF21), gained similar traction as a potential browning agent.…”
Section: Between Brown and White: An Adipocyte For All Seasonsmentioning
confidence: 99%